The Influence of Al-Ma’ṯūrāt Recitation Habituation on Students’ Learning Psychology - Isnaini Pratiwi (Sufiya Journal of Islamic Studies, 2023)
This study aims to analyze the influence of the habitual recitation of Al-Ma’ṯūrāt on students’ learning psychology. A stable and calm psychological condition constitutes a fundamental prerequisite for the optimal absorption of academic material; however, this condition is often hindered by students’ anxiety and lack of concentration. Employing an associative quantitative approach, data were collected through structured questionnaires administered to 24 seventh-grade students at SMP IT Al-Ikhawan. Data analysis was conducted using descriptive statistics, Product Moment correlation analysis, and significance testing (t-test). The findings indicate that students perceived the habitual recitation of Al-Ma’ṯūrāt as providing emotional and mental tranquility. These results demonstrate that the habituation of Al-Ma’ṯūrāt recitation has a significant effect on enhancing students’ psychological calmness and mental readiness for learning. The implications of this study emphasize that the integration of religious activities should not merely be viewed as a formal routine, but rather as an effective classroom management instrument for creating a conducive learning environment. Furthermore, this practice serves as a strategic medium for fostering students’ self-confidence and internalizing positive learning intentions.